Cooling liquid for new energy vehicle and preparation method of cooling liquid
By preparing a new energy vehicle coolant composed of basic liquid, corrosion inhibitor, functional additive, glycol monoethyl ether and defoaming agent, the problem of heat dissipation in the power system of new energy vehicles is solved and the battery performance is achieved protection and security improvement.
Patent Information
- Application Number
- CN202411592378.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
AI Technical Summary
If the heat generated by the power system of a new energy vehicle during operation cannot be dispersed effectively in time, it may lead to reduced battery performance, shortened service life, and even safety problems such as thermal runaway.
Provide a new energy vehicle coolant, which consists of a basic liquid, corrosion inhibitor, functional additive, ethylene glycol monoethyl ether and defoaming agent. Through milling and ultrasonic treatment, excellent high transmission can be prepared. Coolant with thermal and corrosion resistance.
This coolant not only has good corrosion resistance, but also has excellent high heat transfer performance, effectively ensuring its quality and quality, extending battery life, and reducing the risk of thermal runaway.
Smart Images

Figure BDA0005125924740000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coolants, and in particular to a coolant for new energy vehicles and a preparation method thereof. Background Art
[0002] New energy vehicles refer to vehicles that use unconventional automotive fuels as their power source (or use conventional automotive fuels and adopt new on-board power devices), and integrate advanced technologies in vehicle power control and drive to form vehicles with advanced technical principles, new technologies, and new structures.
[0003] Unlike traditional fuel vehicles, the power system of new energy vehicles is mainly composed of batteries, motors and electronic control units. These key components will generate heat during operation. For example, during the charging and discharging process, the battery will generate heat due to the internal electrochemical reaction. If the heat cannot be dissipated in a timely and effective manner, it may lead to battery performance degradation, shortened life, and even safety issues such as thermal runaway.
[0004] Based on this, the present invention provides a new energy vehicle coolant and a preparation method thereof to solve the above-mentioned technical problems! Summary of the invention
[0005] The purpose of the present invention is to provide a new energy vehicle coolant and a preparation method thereof. The prepared new energy vehicle coolant not only has good corrosion resistance, but also has excellent high heat transfer performance, effectively ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a coolant for new energy vehicles, which is composed of the following raw materials in parts by weight: 40 to 50 parts of base liquid, 3 to 6 parts of corrosion inhibitor, 3 to 5 parts of functional additive, 2 to 4 parts of ethylene glycol monoethyl ether and 4 to 7 parts of defoaming agent.
[0008] The present invention is further configured as follows: the base liquid is formed by mixing ethylene glycol and deionized water in a volume ratio of 1:1.3 to 2.3.
[0009] The present invention is further configured as follows: the preparation process of the corrosion inhibitor is as follows:
[0010] The silica aerogel is placed in a muffle furnace and heated, and then kept warm for 100 to 120 minutes to obtain a calcined powder;
[0011] The calcined powder is placed in a composite solution at a solid-liquid ratio of 0.05-0.08 g / mL, and treated at 50-60° C. and 800-1000 r / min for 22-24 hours. After centrifugation, the obtained product is washed 2-4 times with anhydrous ethanol and deionized water respectively, and then dried at 60-70° C. to constant weight to obtain a corrosion inhibitor.
[0012] The present invention is further configured as follows: the heating rate is 10-12°C / min.
[0013] The present invention is further configured as follows: the composite solution is prepared by mixing the composite material and anhydrous ethanol in a mass ratio of 1:22-25.
[0014] The present invention is further configured as follows: the composite material is prepared by mixing methyl methacrylate and benzotriazole in a mass ratio of 1:5 to 6.
[0015] The present invention is further configured as follows: the preparation process of the functional additive is as follows:
[0016] The base material is placed in ethanol at a solid-liquid ratio of 0.01 to 0.05 g / mL, treated at 8000 to 12000 r / min for 20 to 30 minutes, nano silicon nitride fibers are added thereto, and treated at 200 to 210°C for 5 to 6 hours;
[0017] After cooling, the suspension is filtered, and the obtained filter cake is placed in deionized water at a mass ratio of 1:6-7, treated at 80-100 r / min for 10-12 minutes, filtered, and dried at 40-50° C. to constant weight to obtain a functional additive;
[0018] Wherein, the added amount of the nano silicon nitride fiber is 180-200% of the mass of the base material.
[0019] The present invention is further configured as follows: the preparation process of the base material is as follows:
[0020] Place 60-mesh wheat straw powder in distilled water at a solid-liquid ratio of 0.42-0.52 g / mL, treat at 320-340°C for 20-26 min, cool, wash with deionized water 2-4 times, centrifuge at 10000-12000 r / min for 20-22 min, collect the supernatant, and filter;
[0021] The obtained filtrate was freeze-dried to obtain a base material.
[0022] The present invention is further configured as follows: the defoaming agent is selected from any one of defoaming agent PE6100 and defoaming agent TERGITOLL61.
[0023] The second aspect of the present invention: also provides a method for preparing the above-mentioned new energy vehicle coolant, comprising the following steps:
[0024] Step 1, accurately weighing the base liquid, the corrosion inhibitor, the functional additive, ethylene glycol monoethyl ether and the defoaming agent, and respectively placing the corrosion inhibitor and the functional additive in a grinding device for grinding treatment to obtain pretreated corrosion inhibitors and functional additives;
[0025] Step 2: placing the base liquid, ethylene glycol monoethyl ether, the pretreated corrosion inhibitor and the functional additive in a mixing device for ultrasonic treatment for 20 to 30 minutes, then adding a defoaming agent, treating at 120 to 140 r / min for 5 to 8 minutes, and adjusting the pH to 7.5 to 11.0;
[0026] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain the finished product of the coolant for new energy vehicles.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] In the present invention, base liquid, corrosion inhibitor, functional additive, ethylene glycol monoethyl ether and defoamer are used as raw materials, and the corrosion inhibitor and functional additive are respectively placed in a grinding device for grinding treatment to obtain pretreated corrosion inhibitor and functional additive, and then the base liquid, ethylene glycol monoethyl ether, pretreated corrosion inhibitor and functional additive are placed in a mixing device for ultrasonic treatment, and then a defoamer is added, and the pH value is adjusted; finally, after the mixing is completed, the material is discharged, and then the inspection and metering packaging steps are carried out in sequence to finally obtain the finished product of the coolant for new energy vehicles. The coolant for new energy vehicles prepared by the present invention not only has good corrosion resistance, but also has excellent high heat transfer performance, which effectively guarantees its quality. The coolant for new energy vehicles and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] The present embodiment provides a coolant for new energy vehicles, which is composed of the following raw materials in parts by weight: 40 parts of base liquid, 3 parts of corrosion inhibitor, 3 parts of functional additive, 2 parts of ethylene glycol monoethyl ether and 4 parts of defoaming agent.
[0032] The base liquid is prepared by mixing ethylene glycol and deionized water in a volume ratio of 1:1.3.
[0033] The preparation process of corrosion inhibitor is as follows:
[0034] The silica aerogel was placed in a muffle furnace and heated, and then kept warm for 100 minutes to obtain a calcined powder;
[0035] The calcined powder was placed in a composite solution at a solid-liquid ratio of 0.05 to 0.08 g / mL, and treated at 50° C. and 800 r / min for 22 hours. After centrifugation, the obtained product was washed twice with anhydrous ethanol and deionized water, respectively, and then dried at 60° C. to constant weight to obtain a corrosion inhibitor.
[0036] Furthermore, the heating rate is 10°C / min.
[0037] The composite solution is prepared by mixing the composite material and anhydrous ethanol in a mass ratio of 1:22.
[0038] Furthermore, the composite material is prepared by mixing methyl methacrylate and benzotriazole in a mass ratio of 1:5.
[0039] In this embodiment, it should be noted that the silica aerogel was purchased from Anhui High Quality New Energy Technology Co., Ltd.
[0040] The preparation process of the functional additive is as follows:
[0041] The base material was placed in ethanol at a solid-liquid ratio of 0.01 g / mL, treated at 8000 r / min for 20 min, nano silicon nitride fibers were added thereto, and treated at 200°C for 5 h;
[0042] After cooling, the suspension was filtered, and the obtained filter cake was placed in deionized water at a mass ratio of 1:6, treated at 80 r / min for 10 min, filtered, and dried at 40° C. to constant weight to obtain a functional additive;
[0043] Wherein, the added amount of the nano silicon nitride fiber is 180% of the mass of the base material.
[0044] Further, the preparation process of the base material is as follows:
[0045] 60-mesh wheat straw powder was placed in distilled water at a solid-liquid ratio of 0.42 g / mL, treated at 320°C for 20 min, cooled, washed twice with deionized water, centrifuged at 10,000 r / min for 20 min, and the supernatant was collected and filtered;
[0046] The obtained filtrate was freeze-dried to obtain a base material.
[0047] The defoaming agent used is defoaming agent PE6100.
[0048] In this embodiment, it should be noted that the nano silicon nitride fibers were purchased from Suzhou Kaifa New Material Technology Co., Ltd.
[0049] In addition, this embodiment also provides a method for preparing the above-mentioned new energy vehicle coolant, comprising the following steps:
[0050] Step 1, accurately weighing the base liquid, the corrosion inhibitor, the functional additive, ethylene glycol monoethyl ether and the defoaming agent, and respectively placing the corrosion inhibitor and the functional additive in a grinding device for grinding treatment to obtain pretreated corrosion inhibitors and functional additives;
[0051] Step 2: Place the base liquid, ethylene glycol monoethyl ether, pretreated corrosion inhibitor and functional additive in a mixing device for ultrasonic treatment for 20 minutes, then add a defoaming agent, treat at 120 r / min for 5 minutes, and adjust the pH to 7.5;
[0052] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain the finished product of the coolant for new energy vehicles.
[0053] Example 2
[0054] The preparation method of the new energy vehicle coolant provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the new energy vehicle coolant in this embodiment are different; the specific raw material composition and the specific preparation method of the new energy vehicle coolant in this embodiment are as follows:
[0055] The present embodiment provides a coolant for new energy vehicles, which is composed of the following raw materials in parts by weight: 45 parts of base liquid, 4 parts of corrosion inhibitor, 4 parts of functional additive, 3 parts of ethylene glycol monoethyl ether and 5 parts of defoaming agent.
[0056] The base liquid is prepared by mixing ethylene glycol and deionized water in a volume ratio of 1:1.8.
[0057] The preparation process of corrosion inhibitor is as follows:
[0058] The silica aerogel was placed in a muffle furnace and heated, and then kept warm for 110 minutes to obtain a calcined powder;
[0059] The calcined powder was placed in a composite solution at a solid-liquid ratio of 0.06 g / mL and treated at 55°C and 900 r / min for 23 hours. After centrifugation, the obtained product was washed three times with anhydrous ethanol and deionized water respectively, and then dried at 65°C to constant weight to obtain a corrosion inhibitor.
[0060] Furthermore, the heating rate was 11°C / min.
[0061] The composite solution is prepared by mixing the composite material and anhydrous ethanol in a mass ratio of 1:23.
[0062] Furthermore, the composite material is prepared by mixing methyl methacrylate and benzotriazole in a mass ratio of 1:5.
[0063] In this embodiment, it should be noted that the silica aerogel was purchased from Anhui High Quality New Energy Technology Co., Ltd.
[0064] The preparation process of the functional additive is as follows:
[0065] The base material was placed in ethanol at a solid-liquid ratio of 0.03 g / mL, treated at 10,000 r / min for 25 min, nano silicon nitride fibers were added thereto, and treated at 205°C for 6 h;
[0066] After cooling, the suspension was filtered, and the obtained filter cake was placed in deionized water at a mass ratio of 1:6, treated at 90 r / min for 11 min, filtered, and dried at 45° C. to constant weight to obtain a functional additive;
[0067] Wherein, the added amount of the nano silicon nitride fiber is 190% of the mass of the base material.
[0068] Further, the preparation process of the base material is as follows:
[0069] 60-mesh wheat straw powder was placed in distilled water at a solid-liquid ratio of 0.47 g / mL, treated at 330°C for 23 min, cooled, washed with deionized water three times, centrifuged at 11000 r / min for 21 min, and the supernatant was collected and filtered;
[0070] The obtained filtrate was freeze-dried to obtain a base material.
[0071] The defoaming agent used is TERGITOLL61.
[0072] In this embodiment, it should be noted that the nano silicon nitride fibers were purchased from Suzhou Kaifa New Material Technology Co., Ltd.
[0073] In addition, this embodiment also provides a method for preparing the above-mentioned new energy vehicle coolant, comprising the following steps:
[0074] Step 1, accurately weighing the base liquid, the corrosion inhibitor, the functional additive, ethylene glycol monoethyl ether and the defoaming agent, and respectively placing the corrosion inhibitor and the functional additive in a grinding device for grinding treatment to obtain pretreated corrosion inhibitors and functional additives;
[0075] Step 2: Place the base liquid, ethylene glycol monoethyl ether, pretreated corrosion inhibitor and functional additive in a mixing device for ultrasonic treatment for 25 minutes, then add a defoaming agent, treat at 130 r / min for 6 minutes, and adjust the pH to 9;
[0076] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain the finished product of the coolant for new energy vehicles.
[0077] Example 3
[0078] The preparation method of the new energy vehicle coolant provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the new energy vehicle coolant in this embodiment are different; the specific raw material composition and the specific preparation method of the new energy vehicle coolant in this embodiment are as follows:
[0079] The present embodiment provides a coolant for new energy vehicles, which is composed of the following raw materials in parts by weight: 50 parts of base liquid, 6 parts of corrosion inhibitor, 5 parts of functional additive, 4 parts of ethylene glycol monoethyl ether and 7 parts of defoaming agent.
[0080] The base liquid is a mixture of ethylene glycol and deionized water in a volume ratio of 1:2.3.
[0081] The preparation process of corrosion inhibitor is as follows:
[0082] The silica aerogel was placed in a muffle furnace and heated, and then kept warm for 120 minutes to obtain a calcined powder;
[0083] The calcined powder is placed in a composite solution at a solid-liquid ratio of 0.05-0.08 g / mL, and treated at 60° C. and 800-1000 r / min for 24 hours. After centrifugation, the obtained product is washed 2-4 times with anhydrous ethanol and deionized water respectively, and then dried at 60-70° C. to constant weight to obtain a corrosion inhibitor.
[0084] Furthermore, the heating rate was 12°C / min.
[0085] The composite solution is prepared by mixing the composite material and anhydrous ethanol in a mass ratio of 1:25.
[0086] Furthermore, the composite material is prepared by mixing methyl methacrylate and benzotriazole in a mass ratio of 1:6.
[0087] In this embodiment, it should be noted that the silica aerogel was purchased from Anhui High Quality New Energy Technology Co., Ltd.
[0088] The preparation process of the functional additive is as follows:
[0089] The base material was placed in ethanol at a solid-liquid ratio of 0.01 to 0.05 g / mL, treated at 12000 r / min for 30 min, nano silicon nitride fibers were added thereto, and treated at 210°C for 6 h;
[0090] After cooling, the suspension was filtered, and the obtained filter cake was placed in deionized water at a mass ratio of 1:7, treated at 100 r / min for 12 min, filtered, and dried at 50° C. to constant weight to obtain a functional additive;
[0091] Wherein, the added amount of the nano silicon nitride fiber is 200% of the mass of the base material.
[0092] Further, the preparation process of the base material is as follows:
[0093] 60-mesh wheat straw powder was placed in distilled water at a solid-liquid ratio of 0.52 g / mL, treated at 340°C for 26 min, cooled, washed with deionized water 4 times, centrifuged at 12000 r / min for 22 min, and the supernatant was collected and filtered;
[0094] The obtained filtrate was freeze-dried to obtain a base material.
[0095] The defoaming agent used is defoaming agent PE6100.
[0096] In this embodiment, it should be noted that the nano silicon nitride fibers were purchased from Suzhou Kaifa New Material Technology Co., Ltd.
[0097] In addition, this embodiment also provides a method for preparing the above-mentioned new energy vehicle coolant, comprising the following steps:
[0098] Step 1, accurately weighing the base liquid, the corrosion inhibitor, the functional additive, ethylene glycol monoethyl ether and the defoaming agent, and respectively placing the corrosion inhibitor and the functional additive in a grinding device for grinding treatment to obtain pretreated corrosion inhibitors and functional additives;
[0099] Step 2: Place the base liquid, ethylene glycol monoethyl ether, pretreated corrosion inhibitor and functional additive in a mixing device for ultrasonic treatment for 30 minutes, then add a defoaming agent and treat at 140 r / min for 8 minutes, and adjust the pH to 11.0;
[0100] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain the finished product of the coolant for new energy vehicles.
[0101] Comparative Example 1: The difference from Example 1 is that in this example, an equal amount of benzotriazole is used to replace the corrosion inhibitor.
[0102] Comparative Example 2: The difference from Example 1 is that this example does not contain a functional additive.
[0103] Performance test: The new energy vehicle coolant samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the new energy vehicle coolant provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:
[0104] 1. Thermal conductivity test: The test method is to test according to the method specified in ASTM D2717. At 20°C, the thermal conductivity increase rate is calculated. Thermal conductivity increase rate (%) = (thermal conductivity of sample - thermal conductivity of base liquid) / thermal conductivity of base liquid × 100%.
[0105] 2. Corrosion resistance test: The test method is to conduct glassware corrosion tests on various coolants at 20°C according to the test method specified in ASTMD1384.
[0106] The obtained test data are recorded in Table 1 and Table 2 below:
[0107] Table 1 Thermal conductivity test results of each group of coolants
[0108] Group Thermal conductivity increase rate (%) Example 1 Group 86 Example 2 Group 84 Example 3 Group 85 Comparison group 1 76 Comparison of 2 groups 35
[0109] Table 2 Corrosion resistance test results of each group of coolants
[0110]
[0111] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the new energy vehicle coolant prepared by the present invention not only has good corrosion resistance, but also has excellent high heat transfer performance, effectively ensuring its quality. This shows that the new energy vehicle coolant and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0112] In the present invention, the base liquid, corrosion inhibitor, functional additive, ethylene glycol monoethyl ether and defoamer are used as raw materials, and the corrosion inhibitor and functional additive are respectively placed in a grinding device for grinding treatment to obtain pretreated corrosion inhibitor and functional additive, and then the base liquid, ethylene glycol monoethyl ether, pretreated corrosion inhibitor and functional additive are placed in a mixing device for ultrasonic treatment, and then a defoamer is added, and the pH value is adjusted; finally, after the mixing is completed, the material is discharged, and then the inspection and metering packaging steps are carried out in sequence, and finally the finished product of the coolant for new energy vehicles is obtained. The coolant for new energy vehicles prepared by the present invention not only has good corrosion resistance, but also has excellent high heat transfer performance, which effectively guarantees its quality.
[0113] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0114] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A coolant for new energy vehicles, characterized in that: The invention is composed of the following raw materials in parts by weight: 40 to 50 parts of base liquid, 3 to 6 parts of corrosion inhibitor, 3 to 5 parts of functional additive, 2 to 4 parts of ethylene glycol monoethyl ether and 4 to 7 parts of defoaming agent.
2. A new energy vehicle coolant according to claim 1, characterized in that: The base liquid is prepared by mixing ethylene glycol and deionized water in a volume ratio of 1:1.3 to 2.
3.
3. The coolant for new energy vehicles according to claim 1, characterized in that: The preparation process of the corrosion inhibitor is as follows: The silica aerogel is placed in a muffle furnace and heated, and then kept warm for 100 to 120 minutes to obtain a calcined powder; The calcined powder is placed in a composite solution at a solid-liquid ratio of 0.05-0.08 g / mL, and treated at 50-60° C. and 800-1000 r / min for 22-24 hours. After centrifugation, the obtained product is washed 2-4 times with anhydrous ethanol and deionized water respectively, and then dried at 60-70° C. to constant weight to obtain a corrosion inhibitor.
4. The coolant for new energy vehicles according to claim 3, characterized in that: The heating rate is 10-12°C / min.
5. The coolant for new energy vehicles according to claim 3, characterized in that: The composite solution is prepared by mixing the composite material and anhydrous ethanol in a mass ratio of 1:22-25.
6. The coolant for new energy vehicles according to claim 4, characterized in that: The composite material is prepared by mixing methyl methacrylate and benzotriazole in a mass ratio of 1:5-6.
7. The coolant for new energy vehicles according to claim 1, characterized in that: The preparation process of the functional additive is as follows: The base material is placed in ethanol at a solid-liquid ratio of 0.01 to 0.05 g / mL, treated at 8000 to 12000 r / min for 20 to 30 minutes, nano silicon nitride fibers are added thereto, and treated at 200 to 210°C for 5 to 6 hours; After cooling, the suspension is filtered, and the obtained filter cake is placed in deionized water at a mass ratio of 1:6-7, treated at 80-100 r / min for 10-12 minutes, filtered, and dried at 40-50° C. to constant weight to obtain a functional additive; Wherein, the added amount of the nano silicon nitride fiber is 180-200% of the mass of the base material.
8. The coolant for new energy vehicles according to claim 7, characterized in that: The preparation process of the base material is as follows: Place 60-mesh wheat straw powder in distilled water at a solid-liquid ratio of 0.42-0.52 g / mL, treat at 320-340°C for 20-26 min, cool, wash with deionized water 2-4 times, centrifuge at 10000-12000 r / min for 20-22 min, collect the supernatant, and filter; The obtained filtrate was freeze-dried to obtain a base material.
9. The coolant for new energy vehicles according to claim 1, characterized in that: The defoamer is selected from any one of defoamer PE6100 and defoamer TERGITOLL61.
10. The method for preparing a coolant for new energy vehicles according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, accurately weighing the base liquid, the corrosion inhibitor, the functional additive, ethylene glycol monoethyl ether and the defoaming agent, and respectively placing the corrosion inhibitor and the functional additive in a grinding device for grinding treatment to obtain pretreated corrosion inhibitors and functional additives; Step 2: placing the base liquid, ethylene glycol monoethyl ether, the pretreated corrosion inhibitor and the functional additive in a mixing device for ultrasonic treatment for 20 to 30 minutes, then adding a defoaming agent, treating at 120 to 140 r / min for 5 to 8 minutes, and adjusting the pH to 7.5 to 11.0; Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain the finished product of the coolant for new energy vehicles.